Exact and Approximate Maximin Share Allocations in Multi-Graphs - Christodoulou, George; Mastrakoulis, Symeon (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
We study the problem of (approximate) maximin share (MMS) allocation of indivisible items among a set of agents. We focus on the graphical valuation model, in which the input is given by a graph where edges correspond to items, and vertices correspond to agents. An edge may have non-zero marginal value only for its incident vertices. We study additive, XOS and subadditive valuations and we present positive and negative results for (approximate) MMS fairness, and also for (approximate) pair-wise maximin share (PMMS) fairness.